Vapour cloud development in over-filling incidents (FABIG technical note ;, 2013)
Describes an assessment method for calculating the rate at which the volume of a vapour cloud increases during an overfilling incident. The assessment also gives the concentration of hydrocarbons in the cloud and provides some guidance on the extent of cloud spread in relatively flat sites with the kind of obstructions that would be normal in and around a fuel depot tank farm. This Technical Note allows vapour cloud assessment for an overfill of a range of fuels and solvents that are commonly stored in large volumes. Substance/mixture specific equilibrium thermodynamic analysis of air/liquid mixtures in humid atmospheres has been conducted and an empirical correlation and constants are provided that will allow the vapour concentration at the foot of the overfill cascade to be predicted. Whilst the HSE VCA method was developed for vapour cloud development resulting from overfills in calm conditions, this Technical Note gives some preliminary guidance on extending the assessment to low (non-zero) wind speeds and to calculating the rate at which a cloud may accumulate in the case of spray releases (e.g. flange failure or pipe rupture).